2013
DOI: 10.1103/physrevc.88.035206
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Pietarinen expansion method into the single-channel pole extraction problem

Abstract: We present a new approach to quantifying pole parameters of single-channel processes based on a Laurent expansion of partial-wave T-matrices in the vicinity of the real axis. Instead of using the conventional power-series description of the non-singular part of the Laurent expansion, we represent this part by a convergent series of Pietarinen functions. As the analytic structure of the non-singular part is usually very well known (physical cuts with branch points at inelastic thresholds, and unphysical cuts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 23 publications
1
86
0
Order By: Relevance
“…It was later used by a number of authors for solving various problems in scattering and field theory [25], but not applied to the pole search prior to our recent study [13]. A more detailed discussion of the use of conformal mapping, and this method in particular, can be found in Refs.…”
Section: B Pietarinen Seriesmentioning
confidence: 99%
See 4 more Smart Citations
“…It was later used by a number of authors for solving various problems in scattering and field theory [25], but not applied to the pole search prior to our recent study [13]. A more detailed discussion of the use of conformal mapping, and this method in particular, can be found in Refs.…”
Section: B Pietarinen Seriesmentioning
confidence: 99%
“…In our principal paper [13] we have tested the validity of the model on a number of well known πN amplitudes, and concluded that the method is very robust and stable. However, in that paper we did not present an error analysis, deferring it to the forthcoming paper.…”
Section: B Error Analysismentioning
confidence: 99%
See 3 more Smart Citations